1995
DOI: 10.1111/j.1751-1097.1995.tb09141.x
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Reactions of Azidocoumarins

Abstract: Abstract— Photochemical reactions of 6‐azidocoumarin and 7‐azido‐4‐methylcoumarin in the presence of secondary amines have been investigated for their potential applications in photoaffinity labeling. It was found that the singlet nitrene generated from 6‐azidocoumarin isomerized to a dehydroazepine intermediate that reacted with an amine to yield two isomeric adducts. Photolysis of 7‐azido‐4‐meth‐ylcoumarin, in contrast, gave a triplet nitrene that abstracted hydrogen atoms from secondary amine molecules to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Interestingly, the fluorescence signal showed that only the new peak at 5.69 mins was significantly fluorescent and that this product of photoactivation was the reduced Fuco‐NH 2 −F 3 ‐coumarin molecule 13 , likely resulting from the nitrene hydrolysis in buffer. This is consistent with the previous observation that nonfluorinated 7‐azido‐coumarins can yield their 7‐amino counterpart through photolysis and hydrogen atom abstraction [15b] . This experiment also suggests that the fluorogenic conversion does not proceed with quantitative yield which was largely expected based on previous report of a maximum 10 to 30 % yield for photo‐crosslinking of standard aryl azides [23] .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the fluorescence signal showed that only the new peak at 5.69 mins was significantly fluorescent and that this product of photoactivation was the reduced Fuco‐NH 2 −F 3 ‐coumarin molecule 13 , likely resulting from the nitrene hydrolysis in buffer. This is consistent with the previous observation that nonfluorinated 7‐azido‐coumarins can yield their 7‐amino counterpart through photolysis and hydrogen atom abstraction [15b] . This experiment also suggests that the fluorogenic conversion does not proceed with quantitative yield which was largely expected based on previous report of a maximum 10 to 30 % yield for photo‐crosslinking of standard aryl azides [23] .…”
Section: Resultssupporting
confidence: 92%
“…Setting out to measure photophysical properties of both the azido‐F 3 ‐coumarin probe 12 and the amino‐F 3 ‐coumarin probe 13 , we measured the absorption spectra of various concentration of both molecules. We observed absorption maxima of 340 nm and 380 nm for the azido probe 12 and the amino probe 13 respectively (Figure 2a) which is about 10 to 20 nm red‐shifted as compared to reported data for non‐fluorinated analogs [15b] . Importantly, photo‐crosslinkers that show absorption maxima at higher wavelengths (>300 nm) enable milder activation in complex biological samples.…”
Section: Resultssupporting
confidence: 63%
“…Therefore, oppositely, the H 2 S concentration in the cells should be increased from the edge to the center. To support this, we have used a commercial probe 7‐azido‐4‐methylcoumarin to confirm that the hypoxia condition really generated an H 2 S gradient in RAW 264.7 cells under the covered glass plate (see section 6, Supporting Information) [41–44] . Our H 2 S sensing results are shown in Figure 4b, in which 6CN−7N 3 Q (20 μM) is added to the RAW 264.7 cells contained petri dish covered by the glass plate.…”
Section: Resultsmentioning
confidence: 84%
“…To support this, we have used a commercial probe 7-azido-4-methylcoumarin to confirm that the hypoxia condition really generated an H 2 S gradient in RAW 264.7 cells under the covered glass plate (see section 6, Supporting Information). [41][42][43][44] Our H 2 S sensing results are shown in Figure 4b, in which 6CNÀ 7N 3 Q (20 μM) is added to the RAW 264.7 cells contained petri dish covered by the glass plate. As can be seen, the reduced 6CNÀ 7AQ emission intensity at the center of the glass plate is~three time as large as that at the edge (see also the image shown in Figure 4a).…”
Section: Namementioning
confidence: 99%
“…Photochemical reactions of 6-azido and 7-azido coumarins have been studied to explore their potential as photo affinity labels [8]. 3-azido coumarins have been employed to generate strongly fluorescent 1, 2, 3-triazolyl coumarins [9] and recently this reaction has been used in non-destructive verification of PNA immobilization [10].…”
Section: Introductionmentioning
confidence: 99%